Diagnostic accuracy of a novel lateral‐flow device in invasive aspergillosis: a meta‐analysis. Issue 7 (July 2015) - Pan, Zhijie; Fu, Mengjiao; Zhang, Jiaojiao; Zhou, Hua; Fu, Yiqi; Zhou, Jianying
Abstract : N/A: A novel lateral‐flow device (LFD) has been invented for use as a diagnostic tool for invasive aspergillosis (IA). We conducted a meta‐analysis to assess the diagnostic accuracy of the device. Published studies that used the European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria and provided sufficient data were included. Two reviewers independently collected the data from each study and assessed the risk bias using the Quality Assessment of Diagnostic Accuracy Studies‐2. The pooled sensitivity, specificity and diagnostic odds ratio (DOR) were computed and reported with a 95 % confidence interval (CI). Seven studies published between 2008 and March 2015 were included. The pooled sensitivity, specificity and DOR for the proven/probable versus no IA cases were 0.86 (95 % CI, 0.76–0.93), 0.93 (95 % CI, 0.89–0.96) and 65.94 (95 % CI, 27.21–159.81) in the LFD test using bronchoalveolar lavage (BAL) fluid, and 0.68 (95 % CI, 0.52–0.81), 0.87 (95 % CI, 0.80–0.92) and 11.90 (95 % CI, 3.54–39.96) in the LFD test using serum. We concluded that the Aspergillus LFD had a good diagnostic value in immunocompromised patients at risk of IA. The BAL LFD might have a better performance than the serum LFD test.